ULASAN PENERAPAN ILMU PENGETAHUAN DAN TEKNOLOGI DI WILAYAH PEDESAAN APPLICATION OF SCIENCE AND TECHNOLOGY AT RURAL AREAS - , Maryadi (Pembangunan Pedesaan, 2006)
The development of rural areas is important for developing countries, because most of the population lives in rural areas and agriculture is the main occupation. Up till now, most of rural people in these countries still live under poverty line. This situation is completely different from rural people in developed countries. Their activities in agriculture bring about the desired results that is prosperity. This prosperity due to science and technology used. It is argued that science and technology is prerequisite to raise income level and prosperity.